Modeling and evaluation of a high‐resolution CMOS detector for cone‐beam CT of the extremities. Issue 1 (27th November 2017) - Cao, Qian; Sisniega, Alejandro; Brehler, Michael; Stayman, J. Webster; Yorkston, John; Siewerdsen, Jeffrey H.; Zbijewski, Wojciech
Abstract : Purpose: Quantitative assessment of trabecular bone microarchitecture in extremity cone‐beam CT (CBCT) would benefit from the high spatial resolution, low electronic noise, and fast scan time provided by complementary metal‐oxide semiconductor (CMOS) x‐ray detectors. We investigate the performance of CMOS sensors in extremity CBCT, in particular with respect to potential advantages of thin (<0.7 mm) scintillators offering higher spatial resolution. Methods: A cascaded systems model of a CMOS x‐ray detector incorporating the effects of CsI:Tl scintillator thickness was developed. Simulation studies were performed using nominal extremity CBCT acquisition protocols (90 kVp, 0.126 mAs/projection). A range of scintillator thickness (0.35–0.75 mm), pixel size (0.05–0.4 mm), focal spot size (0.05–0.7 mm), magnification (1.1–2.1), and dose (15–40 mGy) was considered. The detectability index was evaluated for both CMOS and a‐Si:H flat‐panel detector (FPD) configurations for a range of imaging tasks emphasizing spatial frequencies associated with feature size a obj . Experimental validation was performed on a CBCT test bench in the geometry of a compact orthopedic CBCT system (SAD = 43.1 cm, SDD = 56.0 cm, matching that of the Carestream OnSight 3D system). The test‐bench studies involved a 0.3 mm focal spot x‐ray source and two CMOS detectors (Dalsa Xineos‐3030HR, 0.099 mm pixel pitch) — one with the standard CsI:Tl thickness of 0.7 mm (C700) and one with a custom 0.4 mm thick scintillator (C400). Measurements of modulation transfer function (MTF), detective quantum efficiency (DQE), and CBCT scans of a cadaveric knee (15 mGy) were obtained for each detector. Results: Optimal detectability for high‐frequency tasks (feature size of ~0.06 mm, consistent with the size of trabeculae) was ~4× for the C700 CMOS detector compared to the a‐Si:H FPD at nominal system geometry of extremity CBCT. This is due to ~5× lower electronic noise of a CMOS sensor, which enables input quantum‐limited imaging at smaller pixel size. Optimal pixel size for high‐frequency tasks was <0.1 mm for a CMOS, compared to ~0.14 mm for an a‐Si:H FPD. For this fine pixel pitch, detectability of fine features could be improved by using a thinner scintillator to reduce light spread blur. A 22% increase in detectability of 0.06 mm features was found for the C400 configuration compared to C700. An improvement in the frequency at 50% modulation (f50 ) of MTF was measured, increasing from 1.8 lp/mm for C700 to 2.5 lp/mm for C400. The C400 configuration also achieved equivalent or better DQE as C700 for frequencies above ~2 mm −1 . Images of cadaver specimens confirmed improved visualization of trabeculae with the C400 sensor. Conclusions: The small pixel size of CMOS detectors yields improved performance in high‐resolution extremity CBCT compared to a‐Si:H FPDs, particularly when coupled with a custom 0.4 mm thick scintillator. The results indicate that adoption of a CMOS detector in extremity CBCT can benefit applications in quantitative imaging of trabecular microstructure in humans.